Analysis of Factors Influencing the Quality of Nursing Services at RSUI Madinah Kasembon Malang - Nurcholis; Sentot Imam Suprapto; Byba Melda Suhita (STRADA : Jurnal Ilmiah Kesehatan, 2026)
The best quality of service provided and the development opportunities that nurses have are influenced by the Quality of Nursing Work Life. The study aims to analyze the factors that influence the quality of nursing services. The research design is an analytical survey with a Cross Sectional approach. The number of samples is 57 nurses using simple random sampling. Data analysis of ordinal regression test the results of the study Work life-home life, Work design, Work context Work world in the category of Sufficient.